2014
DOI: 10.1002/2014gl061880
|View full text |Cite
|
Sign up to set email alerts
|

Antarctic Circumpolar Current transport and barotropic transition at Macquarie Ridge

Abstract: Theory and numerical simulations suggest that topographic interactions are central to the dynamics of the Antarctic Circumpolar Current (ACC), but few observations are available to test these ideas. We use direct velocity measurements, satellite altimetry, and an ocean state estimate to investigate the interaction of the ACC with the Macquarie Ridge. Satellite altimeter data show that the Subantarctic Front crosses the ridge through a gap immediately north of Macquarie Island. Yearlong current meter records re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
29
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 39 publications
7
29
0
1
Order By: Relevance
“…This compares with about 14% in the depth-independent component both south of Tasmania (Phillips & Rintoul 2000) and on the Subantarctic Slope (Stanton & Morris 2004). Transport in the SAF through the gaps in Macquarie Ridge is 52 Sv (Rintoul et al 2014), similar to the 48 to 68 Sv found on the Subantarctic Slope (Stanton & Morris 2004).…”
Section: Antarctic Circumpolar Currentsupporting
confidence: 54%
See 1 more Smart Citation
“…This compares with about 14% in the depth-independent component both south of Tasmania (Phillips & Rintoul 2000) and on the Subantarctic Slope (Stanton & Morris 2004). Transport in the SAF through the gaps in Macquarie Ridge is 52 Sv (Rintoul et al 2014), similar to the 48 to 68 Sv found on the Subantarctic Slope (Stanton & Morris 2004).…”
Section: Antarctic Circumpolar Currentsupporting
confidence: 54%
“…The ocean south of the STF is dominated by the eastward flowing Antarctic Circumpolar Current (ACC). Early measurements by Bryden & Heath (1985) on the energetics of the ACC were followed by more measurements around the flanks of the Campbell Plateau (Morris et al 2001) and over the Macquarie Ridge (Rintoul et al 2014). …”
Section: Antarctic Circumpolar Currentmentioning
confidence: 99%
“…Bathymetry affects the number of identifiable branches of the SAF. Its role in minimising meandering and stabilising the flow of the SAF as it passes across ridges has been previously suggested by Sokolov and Rintoul (2007), Rintoul et al (2014) and Chapman and Morrow (2014). It is also consistent with the idea of topographic barriers reducing the number of branches in a front (Thompson et al, 2010;Graham et al, 2012;Thompson and Sallée, 2012;Chapman, 2014).…”
mentioning
confidence: 75%
“…More detailed studies have shown that these fronts are not single static entities, but have multiple branches or filaments that change in position and intensity on different scales (Moore et al, 1999). Higher resolution data analysis has shown that the SAF consists of three branches that extend from the sea surface to the sea floor (e.g., Rintoul, 2007, 2009b;Rintoul et al, 2014). The positions of the three SAF branches are modified by bathymetry in the New Zealand subantarctic region.…”
mentioning
confidence: 99%
See 1 more Smart Citation